State-of-the-art review on responses of combined piled raft foundation subjected to seismic loads using static and dynamic approaches. Issue 169 (June 2023) - Chanda, Diptesh; Saha, Rajib; Haldar, Sumanta; Choudhury, Deepankar
Abstract: Rapid urbanization and the unavailability of suitable ground conditions escalated the demand for high-rise superstructures over the years. Challenges persuaded geotechnical engineers to think of a robust yet economical foundation system that can support these superstructures without compromising their safety and serviceability. The combined piled raft foundation (CPRF) has been distinguished as an effective foundation that regulates the total and differential settlements and considerably improves the overall performance of the whole structure. Substantial pieces of research have been conducted previously to understand the responses of this robust foundation under static vertical loading. A few static loading code provisions are also available to help engineers to practice such foundation systems in real field conditions. In fact, many South-East Asia and European nations have appreciated the conceptualization of CPRF based on their worthwhile functioning reported in various on-field projects. However, design provisions for CPRF under lateral loading are still terse. The present paper, therefore, attempts to critically review contemporary research on the responses of CPRF under lateral loading in different subsoil strata and discusses the importance of soil-structure interaction (SSI) consideration in the seismic design of CPRF. The emphasis of discussion is oriented to several important design aspects of CPRF such as load-sharing, bending moment, peak acceleration, lateral and vertical deformation, period lengthening, etc. A few case studies on the performance of CPRF under seismic conditions are also discussed. The significance of such a study lies in framing constructive design guidelines of CPRF under lateral loading and resting in different subsoil conditions. Highlights: The manuscript presents a state-of-the-art review of responses of CPRF subjected to lateral loading with an emphasis to seismic conditions. The paper discusses the history of CPRF and how this has gathered confidence among practice engineers to use it for mega projects. The paper emphasizes several important design aspects of CPRF such as load-sharing, bending moment response, peak acceleration, etc. A brief insight into a few CPRF projects and the importance of SSI consideration in the seismic design of CPRF are also highlighted. The significance of such a study lies in framing constructive design guidelines of CPRF for different subsoil conditions and load combinations.